DYSPHEMISM USED IN DEADPOOL MOVIE PAPER TITLE - Pretty Sitanggang, Maria Ayu; Setia, Eddy; Ganie, Rohani (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2020)
This thesis entitled Dysphemism Used in Deadpool Movie. Dysphemism in Deadpool is problematized in its home country, i.e. the United States, due to its excessive occurrences. For this reason, this study aims at 1) to find out the types of dysphemism which illuminate the uses of dysphemism, and 2) revealing the functions which explain why the characters utilize such dysphemistic words. The theory of Dysphemism proposed by Allan & Burridge (2006) is used to reveal the functions of the use of dysphemism. In addition, the author also uses a semantic approach by delineating the meaning of dysphemism in a lexical and contextual manner along with examples of its use in context. Moreover, the analysis of componential meaning is used to observe the types of dysphemism based on Allan & Burridge's theory and Rawson's theory. The method used in this research is descriptive qualitative. The data of this research are words and phrases which indicated dysphemism. The sources of the data are transcript and video. There are 95 dysphemism data obtained and observed by the writer. The result of this research shows that three types of dysphemism are found in the movie, i.e. profanity, obscenity, and insult. The dysphemism type mostly found is the obscenity with 31 data (33%). In addition, there are seven functions of the use of dysphemism revealed: to humiliate something or someone else, to express anger, to emphasize thing or condition, to state and represent a very bad thing or condition, to express astonishment or amazement, to show intimacy and to express excitement. The most dominant function of dysphemism that is used in this movie is to humiliate something or someone else with 79 data (83%).